(untitled) (BioMedical Research in Medicine (BMR Medicine) (ISSN 2349-0756), 2024)
Cystic hygroma is a type of lymphangioma which generally seen in infant. In adults,less than 150 cases have been reported in the literature. We present here a case of 27 year old male having giant cystic hygroma in neck with extension into mediastinum